Blinded by the sun: The role of prosumers as niche actors in incumbent firms’ adoption of solar power during sustainability transitions - Weigelt, Carmen; Lu, Shaohua; Verhaal, J. Cameron (Research Policy, 2021)
While extant research discusses how niche innovations develop in protected market niches and trigger regime shifts along sustainability transition pathways, we know less about the direct role of different niche actors as competitors in affecting regime incumbents’ investments in niche innovations. This study addresses this gap and builds on Strategic Niche Management and the Multi-level Perspective to distinguish two different niche actors: prosumers on the demand-side applying a niche innovation in a disruptive way to regime incumbents’ business model, and new entrants on the supply-side applying the niche innovation symbiotically with the regime. We examine incumbent responses to these different niche actors in different competitive and policy environments. Studying the United States’ electricity industry's sustainability transition toward solar from 2010-2017, we find that as more niche actors enter, regime incumbents are more likely to invest in the niche innovation, but the effect is influenced by policy and competitiveness of the environment. In competitive environments, incumbents are more likely to respond to disruptive niche actors (prosumers), while in traditional monopoly-like markets they are more likely to respond to symbiotic niche actors. We also find that the prosumer effect is stronger when the time that policies in support of the niche innovation have existed is shorter, indicating a potential substituting relationship of niche actors and policy. Our work contributes to the extant literature by demonstrating that the interplay between different niche actors needs to be understood within the context of policy, and that considering policy without accounting for the competitive environment may omit an important aspect of how regime actors become active participants in sustainability transitions.